Diagnosis and Treatment of Musculoskeletal Disorders - Runhaar, Jos; van Middelkoop, Marienke (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Musculoskeletal disorders are a serious burden for patients and modern society. In Europe alone, 100,000,000 individuals suffer from musculoskeletal disorders and 40,000,000 affected workers cause losses due to work absence and a productivity loss of EUR 12 billion per year. Worldwide, musculoskeletal disorders are the second most common cause of pain and disability. Adequate diagnosis and early initiation of treatment are key elements in the care for patients suffering from musculoskeletal disorders, yet, for many musculoskeletal disorders, diagnostic tests lack appropriate accuracy. Treatment of musculoskeletal disorders is challenging as the mechanisms causing the complaints and mechanisms of action for the available treatment options are largely unknown. Moreover, these mechanisms and effectiveness might depend on specific patients' characteristics and call for personalized strategies. This Special Issue invited researchers in the field to contribute to the state of the art in the diagnosis and treatment of musculoskeletal disorders. As many different healthcare professionals are involved in the diagnosis and treatment of musculoskeletal disorders, the Special Issue published high-quality studies from different areas of healthcare. Studies reporting on original research (e.g., randomized controlled trials, cohort studies), but also systematic literature reviews and meta-analyses within the scope of the Special Issue were considered. Given recent debates around the effectiveness of surgical interventions for musculoskeletal disorders and concomitant risks for adverse side-effects, intervention studies on non-surgical treatment options were prioritized.